2023
DOI: 10.1101/2023.02.06.527323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting Troponin C with Small Molecules Containing Diphenyl Moieties: Calcium Sensitivity Effects on Striated Muscle and Structure Activity Relationship

Abstract: Despite large investments from academia and industry, heart failure, which results from a disruption of the contractile apparatus, remains a leading cause of death. Cardiac muscle contraction is a calcium-dependent mechanism, which is regulated by the troponin protein complex (cTn) and specifically by the N-terminal domain of its calcium binding subunit (cNTnC). There is an increasing need for the development of small molecules that increase calcium sensitivity without altering systolic calcium concentration, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Dvornikov et al explored the effect of the R145W mutation on myofilament length-dependent activation (LDA) and found that the mutation does not affect LDA but does increase the sensitivity of the myofilament to Ca 2+ . Moreover, biochemical assays and functional experiments on the R145G mutation converged on the finding that this mutation causes an increase in myofilament Ca 2+ -sensitivity , and reduces the ability of cTnI to inhibit activation of cardiac muscle. , Computational efforts have also explored the effect that these cTnI mutations can have on the thermodynamics of the cTnC HP opening event. , Our lab and others have successfully shown the potential of computational tools as a viable option for studying cTn dynamics for the purpose of computationally aided drug discovery and Ca 2+ -binding simulations. …”
Section: Introductionmentioning
confidence: 99%
“…Dvornikov et al explored the effect of the R145W mutation on myofilament length-dependent activation (LDA) and found that the mutation does not affect LDA but does increase the sensitivity of the myofilament to Ca 2+ . Moreover, biochemical assays and functional experiments on the R145G mutation converged on the finding that this mutation causes an increase in myofilament Ca 2+ -sensitivity , and reduces the ability of cTnI to inhibit activation of cardiac muscle. , Computational efforts have also explored the effect that these cTnI mutations can have on the thermodynamics of the cTnC HP opening event. , Our lab and others have successfully shown the potential of computational tools as a viable option for studying cTn dynamics for the purpose of computationally aided drug discovery and Ca 2+ -binding simulations. …”
Section: Introductionmentioning
confidence: 99%
“…MD simulation is a computational method that is used to explore conformational spaces for proteins and ligands and is widely used in studying the behavior of IDPs. 26,27 These in silico approaches are well suited for conformational analysis as they can provide insight into the atomic-level detail of IDPs, other proteins, and complex systems that allow for predicting and understanding biological pathways and their activity. 28 A limitation of using conventional MD is the presence of energy barriers that hinder molecules and residues from transitioning between conformational states.…”
Section: ■ Introductionmentioning
confidence: 99%